LEARNING THROUGH CHILDREN’S PAINTINGS - Muchammad Bayu Tejo Sampurno (Universitas Sebelas Maret, 2017)
Art is one of medium for children to play, with their surroundings with imagination. Art is also a medium of understanding, to help children understand the concepts that are not yet known. with various arguments began to realize the importance of the arts for children, but they do not understand what they need to support his artistic abilities. Artwork created by children classified as special. That is because the children's artwork there are values which constitute the essence and the nature of art itself. From children's artwork, can be taken the science that is important for human beings, namely regarding the personal creative who is not afraid to experiment because the child doesn't pay attention to the existence of factors which often become a problem for adults.